2013
DOI: 10.1088/0963-0252/22/6/065005
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the electron energy distribution function of electron beam generated plasmas with molecular gas concentration: II. Numerical modeling

Abstract: In this work, the second in a series of two, a spatially averaged model of an electron beam generated Ar-N 2 plasma is developed to identify the processes behind the measured influence of trace amounts of N 2 on the development of the electron energy distribution function. The model is based on the numerical solution of the electron Boltzmann equation self-consistently coupled to a set of rate balance equations for electrons, argon and nitrogen species. Like the experiments, the calculations cover only the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…It is noted that the effects of adding molecular H 2 and N 2 gases to monoatomic rare gas Ar plasmas have so far been studied both experimentally and numerically/theoretically (see the Appendix). [107][108][109][110][111][112][113][114][115][116][117][118][119] In the present experiments, we did not measure the T e as well as electron energy distribution function (EEDF), and so we cannot say quantitatively the effects of adding a small amount (<1%) of H 2 and N 2 to Ar on the plasma properties. However, the present optical emission spectroscopy indicated that the addition of <1% H 2 and N 2 to Ar plasmas gave rise to no significant change of the Ar I line intensities in the visible and near-ir region (and thus no significant change of the intensity ratio of the visible Ar I lines to the near-ir ones); this implies that no significant change in the EEDF and/or T e occurred with the H 2 and N 2 addition, since the upper-level excitation energies for visible Ar I lines are >1 eV higher than those of near-ir ones (as mentioned above).…”
Section: Journal Of Applied Physicsmentioning
confidence: 85%
See 2 more Smart Citations
“…It is noted that the effects of adding molecular H 2 and N 2 gases to monoatomic rare gas Ar plasmas have so far been studied both experimentally and numerically/theoretically (see the Appendix). [107][108][109][110][111][112][113][114][115][116][117][118][119] In the present experiments, we did not measure the T e as well as electron energy distribution function (EEDF), and so we cannot say quantitatively the effects of adding a small amount (<1%) of H 2 and N 2 to Ar on the plasma properties. However, the present optical emission spectroscopy indicated that the addition of <1% H 2 and N 2 to Ar plasmas gave rise to no significant change of the Ar I line intensities in the visible and near-ir region (and thus no significant change of the intensity ratio of the visible Ar I lines to the near-ir ones); this implies that no significant change in the EEDF and/or T e occurred with the H 2 and N 2 addition, since the upper-level excitation energies for visible Ar I lines are >1 eV higher than those of near-ir ones (as mentioned above).…”
Section: Journal Of Applied Physicsmentioning
confidence: 85%
“…39 When N 2 is added to Ar, a cooling effect occurs on the plasma electrons, and the electron temperature T e tends to be reduced. [117][118][119] The EEDFs in pure Ar plasmas are nearly Maxwellian below the inelastic collision thresholds with a slight depletion of electrons for energies E e > 11.6 eV [the first excitation threshold for Ar or the excitation energy for Ar*(3p 5 4s 3 P 2 )]; 116 with increasing the fraction of N 2 , a reduction in the EEDF occurs in the range E e ∼ 1-5 eV, owing to some resonant electron-molecule vibrational excitation processes. 112,[116][117][118] In these situations, the electron density n e tends to decrease 116,118 and the gas temperature T g tends to increase 113 with the N 2 fraction.…”
Section: Appendix: Effects Of H 2 and N 2 Addition To Ar Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…They have demonstrated that the main effect of the external EB was the control of rate constant for ionization, excitation, and momentum transfer. Boris and Petrov et al have written a series of two papers to report the control of the EEPF experimentally and theoretically in EB‐generated plasmas, without any conventionally driving electric field. The ability for control of the EEPF has been demonstrated, by adding small admixture of nitrogen to a background argon gas, at pressure of 25 mTorr.…”
Section: Introductionmentioning
confidence: 99%
“…Such a configuration has been proposed and attracted great attention recently. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The groups of Fernsler and Manheimer 1,2 have studied the fundamental physics of the EI generated plasmas. Chen and Eden 3 have realized a microplasma transistor by injecting electrons into the sheath of a plasma with a controllable electron emitter.…”
Section: Introductionmentioning
confidence: 99%